Larch response to warming in northern Siberia - Kharuk, Viacheslav I.; Petrov, Ilya A.; Krivobokov, Leonid V.; Golyukov, Alexey S.; Dvinskaya, Maria L.; Im, Sergei T.; Shushpanov, Alexander S.; Smith, Kevin T. (Regional environmental change)
The dendroecology of larch (Larix gmelinii Rupr.) in the world’s northernmost forest provided insight into the complex relationship of tree growth, forest stand establishment, and changing eco-climatic factors. The Ary-Mas forest in the northern Siberia (72° + NL) is an ecological island, surrounded by tundra. We hypothesized that the environmental constraints that limit larch growth in this harsh habitat include soil moisture and winter winds as well as low air temperature. We constructed and analyzed the larch growth index (GI) chronology from the eighteenth century until 2019. We found that the larch GI depended on the air temperature, soil moisture anomalies, and winter wind speed, and that dependence was significantly different before and after the 2000s. Larch GI responded to the onset of climatic warming in the 1970s by a minor GI increase followed by a GI decrease until the end of 1990. Increased air temperature early in the growing season favored increased GI, whereas elevated winter wind speed negatively influenced larch growth. After warming in the 2000s, the length of the growing season increased by 15 days, and larch GI was sensitive to air temperature both early and late in the growing season. The adverse influence of winter winds has gradually decreased since the 1970s, becoming a minor factor in the 2000s. Soil moisture in “wet, cold soils” negatively influenced larch growth. Meanwhile, decreased soil moisture in the northern lowlands favored increased larch growth. We found that larch growth increases were strongly correlated with GPP and NPP (gross and net primary productivity) within the Ary-Mas site and for the central Siberian Arctic. We infer that this Arctic region continues to be a carbon sink.